A Quantitative Investigation: How WorkLife Balance and Job Crafting Shape Teacher Performance - Sherly, Sherly; Marlina Sihombing, Humiras Betty; Gultom, Syawal; Dharma, Edy (Jurnal Ilmu Pendidikan dan Humaniora, 2026)
Teacher performance constitutes a critical determinant of educational effectiveness and institutional quality. Within contemporary educational settings, the capacity to maintain an equilibrium between professional responsibilities and personal life (work life balance) as well as the proactive modification of work roles to align with one’s strengths and preferences (job crafting) are increasingly recognized as influential factors shaping teacher outcomes. This study investigates the extent to which work–life balance and job crafting affect the performance of teachers at Sultan Agung Private Junior High School Pematangsiantar. Employing a quantitative research design with a survey approach, data were gathered from 31 teachers through a structured Likert-scale questionnaire and subsequently analyzed using multiple linear regression. The findings reveal that work–life balance exerts a positive and statistically significant effect on teacher performance, whereas job crafting demonstrates a positive yet statistically insignificant contribution. Collectively, both predictors account for 64% of the variance in teacher performance. These results underscore the dominant role of work–life balance as a determinant of performance within private educational institutions and suggest that job crafting may require stronger organizational facilitation to manifest its potential impact. The study recommends that school administrators strengthen policies that support work–life balance and cultivate organizational conditions that enable teachers to engage more effectively in adaptive job crafting practices.